Socio-Environmental Conflict in the Construction of a Power Plant in Spain S Basque Country: Strategies, Expertise and Certifications - Baigorrotegui-Baigorrotegui, G (Routledge, 2015)
Social and anthropological studies show a growing number of conflicts surrounding energy projects, as governments and companies insist on their implementation despite the concerns of local actors about their perceived socio-environmental risks. In this context, the purpose of this paper is to analyse the politicisation of expertise and certifications in a conflict over the construction of a combined cycle power plant by linking strategic assumptions from two particular sociological approaches. The first approach is based on the study of frame alignment in social movement organisations and the second on the translating interests in actor–network theory. These linked premises are examined in the conflict arising from the construction of a combined cycle natural gas plant in Boroa, in the Basque Country of Spain. This case study brings to light interesting findings on the strategies of the different agencies, certifications, politicisation of expertise and the increasing hostility in local conflicts. © 2013. Taylor & Francis.